Trends of journalists and consumers about the phenomenon of food fraud - Muhamad Al-Bayaa, Mahdi; Selman Al-Rubaye, Laith; Husain Tawina, Ali (ALBAHITH ALALAMI, 2005)
Food comes after air and water in terms of importance in the survival of human beings, In addition, it is the support and strength of health and support, if lost or destroyed man would die or get sick and become a heavy burden on himself and his society. Food, like other sources of life, is subject to various risks and corruption comes from countless sources. Among these dangers is the result of spontaneousness, lack of knowledge or compulsion due to the interaction of variables beyond the will of the producer and the consumer, such as pollution of water, air and environment and their reflection on food consumed by people. However, we can’t deny that some reasons of corruption are intentional and resulting from a planning in advance in order to make an illegal profit at the expense of people's health and safety. The importance of provision of food these days has increased as the number of sources of fraud and manipulation of its components has increased, not to mention the variety of cheating and scamming methods that accompany it from the factory until it reaches the consumer. Increasing the population and increasing the need to feed millions of people in different countries of the land led to an increase in quantities of materials transferred, pre-processed and packed, which are prepared through complex manufacturing processes and go through multiple hands starting from the farm to shipping then factory and storage and finally supply in the wholesale and retail markets. There is no question that all those who follow the food chain have interests and goals that come primarily from profit. It is not surprising that many of them seek to maximise their personal benefit and avoid potential losses, even at the expense of consumers. Here comes the role of the important mediator in the transfer of knowledge and warning, which warns of dangers resulting from consumption of adulterated food and there is no doubt that various media are the main role of this mediator in contemporary society. A thorough understanding of consumer behavior will provide marketing managers with a better idea of ​​how marketing activity works and help them develop a more efficient and capable marketing strategies. Predictability of consumers' behavior and purchasing motivations that reflect their desires and needs will help develop appropriate marketing policies. Future consumer behavior can provide information and insight into consumer decisions, allowing to identify the relationship between attitudes of consumers and journalists towards the phenomenon of cheating in food. We hope this research would provide an objective picture of these trends and study the relationship between perception and knowledge of journalists about the phenomenon under study and the impact on attitudes of consumers, also to indicate the success of press in raising awareness and guidance of the audience by analyzing the press coverage of this phenomenon during the research period. This research aims to reach an answer to a number of questions related to the trends of consumers and journalists about the phenomenon of the lack of food. These questions relate in fact to the basic components of trends, specifically the behavioral and cognitive aspects and related views. The Iraqi press in the field of combating the phenomenon of cheating in food stuffs, whether through identification of the mechanism of work or through the technology of this phenomenon in 2001.